Pre-service Biology teacher’s Perception about Evolution Learning at Senior High School: A Case Study of Biology Education Students’ at Universitas Sebelas Maret Surakarta - Alanindra Saputra (Bioeducation Journal, 2017)
Evolution is one of biology material that learn in senior high school. Many differences on understanding evolution theory give effect this material cannot be taught optimally. The main factor that cause it is religiousity and the low of teachers’ background knowledge. This research conducted to analyze biology preservice teacher about evolutionary learning at senior high school. This descriptive research did at Biology Education Study Program, Universitas Sebelas Maret Surakarta on August 2016 until January 2017. Population were students of Biology Education Study Program Universitas Sebelas Maret Surakarta on semester five in academic year 2015/2016 that took evolutionary course in two parallel class with total 47 students. Sampling used total sampling. Data was the result of students’ last paper analysis. The result showed that 100% students said that evolution material is needed and important to teach for senior high school students; with various reason. For the method of teaching evolution, 75% students suggest that evolution should be teach by some interesting methods. Furthermore, students (±20%) also gave opinion that evolution can be taught by using prehistoric site, such as Sangiran and Trinil to give direct experience to them.